Prioritising significant characteristics of green roof systems in Malaysia urban area / Danish Hakim Ahmad Fadli and Shafikah Saharuddin - Ahmad Fadli, Danish Hakim; Saharuddin, Shafikah (2023)
Green roof systems are a type of sustainable construction that involves planting vegetation on the roofs of buildings. They have multiple benefits for the environment, such as reducing stormwater runoff, improving air quality, mitigating urban heat island effect, and enhancing biodiversity. However, they also pose some challenges and risks, such as increased structural load, fire hazard, water leakage, and maintenance cost. Therefore, it is important to identify and evaluate the significant characteristics of green roof systems that affect their sustainable, durability, and life cycle. These characteristics include the type and depth of growing medium, the selection of vegetation, the drainage layer and irrigation system, the protective layer, and the structural support. The survey is conducted by using questionnaire distributed to 118 contractors in Kuala Lumpur and Putrajaya. The data collection of 49 out of 118 questionnaires was tabulated, interpreted, and analyzed using Statistical Packages for Social Science (SSPS) version 26. As a result, there are six significant characteristics of green roof systems are identified and ranked. The results showed that the most significant maintenance criteria of the green roof are structural support, followed by drainage system, waterproofing membrane, vegetation or plant selection, irrigation system, and lightweight growth medium. The findings of the study can serve as added value to existing practice. Therefore, it will also help to improve current green roof implementation in the Malaysia urban areas.